Assessment of P wave duration and P wave dispersion in high level football referees - Yucesir, I.; Sahin Yildiz, B.; Coskun, O.; Yakal, S.; Bayraktar, B.; Metin, G.; Altan, M.; Yildiz, M. (The Journal of Sports Medicine and Physical Fitness, 2016)
P wave dispersion and P wave maximal duration reflect the activation of atrial muscle and is influenced by the mass of the excited tissue. It may reflect atrial remodelling, most likely atrial fibrosis. The purpose of this study is to measure P wave duration and P wave dispersion in the high level football referees. We recruited 104 elite and national referees with a training history of many years. The control group was made of 32 healthy sedentary subjects. The difference between P maximum and P minimum durations was defined as P wave dispersion. Echocardiographic parameters such as left atrial diameter were assessed with a Vivid 3 cardiovascular ultrasound system [3S sector probe (1.5--3.6 MHz), GE]. P wave maximum duration, P wave dispersion, left ventricle posterior wall thickness, inter--ventricular septum thickness and left atrial diameter were increased in the football referees as compared with healthy sedentary subjects. There were significant correlations of P wave dispersion with left atrial diameter and left ventricle posterior wall thickness. P wave maximum duration, P wave dispersion and left atrial diameter were increased in the football referees. Also, there was a significant correlation between P wave dispersion and left atrial diameter